Optimum Condition of Inulinase Production from Bacillus cereus (Be9) - A. Ghadbaan, Fatema; Burhan Aldeen, Sanaa (Iraqi Journal of Science, 2023)
Fifty isolates of Bacillus spp were obtained from rhizosphere soil of compositaeplant roots. The ability of inulinase production by these isolates was screened.Bacillus Be9, which isolated from soil of lettuce root, was the highest inulinaseproducer; it was identified as Bacillus cereus. Optimal culture medium andcondition for inulinase production were determinatd; the highest inulinaseproduction was obtained when the bacteria was cultured in inulin medium whichcontained 0.5% inulin, 0.4% peptone as carbon and nitrogen source at pH 7.0inoculated with 1ml of bacterial suspension and incubated at 40˚C for 48hrs.